1993
DOI: 10.1246/cl.1993.2157
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Synthesis of α,α′-Bis(substitutedbenzylidene)cycloalkanones

Abstract: The Cp2TiPh2-catalyzed reaction of cyclopentanone or cyclohexanones with benzaldehydes brought about the cross-aldol condensation to give the corresponding 2,5-bis(substitutedbenzylidene)cyclopentanones or 2,6-bis(substitutedbenzylidene)cyclohexanones in good yields under milder conditions than those previouly reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Early transition metal complexes play an important role in the (selective) transformation of ketones [1], such as the reduction [2], hydrosilylation [3], olefination [4], the addition of metal-alkyl fragments [5], the Aldol condensation [6] and the reductive coupling to form diols (pinacol coupling) [7]. It is expected that the initial step in these transformations is the coordination of the substrate via oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Early transition metal complexes play an important role in the (selective) transformation of ketones [1], such as the reduction [2], hydrosilylation [3], olefination [4], the addition of metal-alkyl fragments [5], the Aldol condensation [6] and the reductive coupling to form diols (pinacol coupling) [7]. It is expected that the initial step in these transformations is the coordination of the substrate via oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional acid-or base-catalyzed reactions often suffer from reverse and side reactions and therefore give low yields of products [8]. Cp 2 TiPh 2 [9] and anhydrous RuCl 3 [10] are reported to give good yields of enone products, but require longer reaction times and high temperatures (120 °C) in sealed, ampoules and tubes, whereas Rh-porphyrin complex-catalyzed reactions reported to give 30% cross-Aldol product [11]. Microwave assisted syntheses [12] using KF/Al 2 O 3 and BMPTO and several catalytic procedures [13] using different complexes of metal ions as catalysts have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The general approach involves cross-aldol condensation of a cycloalkanone with an aromatic aldehyde [11], commonly catalysed by a base [12] or an acid [13], (Scheme 1). Subsequently improved methodologies have been reported that used various reagents/Lewis acids such as (EtO) 4 Si/CsF or KF [14], Cp 2 ZrH 2 -NiCl 2 [15], Rh(III)-porphyrin [16], Cp 2 TiPh 2 [17], BMPTO under microwave irradiation [18], RuCl 3 [19], TiCl 3 OTf [20], FeCl 3 -[bmim] [BF 4 ] [21,22], SmI 3 [23], KF-Al 2 O 3 under ultrasound irradiation [24], TMSCl-NaI [25], H 2 SO 4 -SiO 2 [26], Yb(OTf) 3 [27], Et 2 NTMS-LPDE [28], and [(Me 3 Si) 2 N] 3 Ln(-Cl)Li(THF) 3 under microwave irradiation [29]. However, one or more of the disadvantages such as the use of costly catalysts, use of hazardous agents (nickel compounds are toxic, perchlorates are potentially explosive, silica sulfuric acid is corrosive etc.…”
Section: Introductionmentioning
confidence: 99%